CRITICAL DISCOURSE ANALYSIS OF REPORTING RELATED TO THE ROLE OF THE KALBAR GOVERNMENT AT WWW.ANTARAKALBAR.COM - Zahra, Queena Az; Heryana, Nanang; Syahrani, Agus (Universitas Tanjungpura, 2023)
This research was conducted by analyzing the news which aims to find out the pros and cons of the news and the ideology represented in the eight news stories with the issue of the role of the West Kalimantan government in the ANTARA Kalbar National News Agency (LKBN). The method used in this research is a descriptive method with a qualitative research form. The source of data in this study is the Head of the Bureau between Kalber and Journalists. The techniques used in this research were intervienote-takingking and collecting documents or archives. The tools used in this study were a list of questions, notebooks, stationery, and recording devices which were also used for documentation, namely devices. Based on the results of news analysis from June to July using critical discourse analysis in www.kalbar.antaranews.com, it can be seen that the media conveysnews truthfully and the ideology that is deliberately used is the ideology of subjectivity and nationalism. As well as from this analysis itn be pimplemented learning Indonesian at the junior high school level.